CSA and CIS technologies portfolio: Access and use. A portfolio of the CSA & CIS innovations accessed and used by small-scale farmers in Kenya under the AICCRA project - Nduah, Alex; Ogutu, Liz; Nzuki, Esther; Waswa, Boaz (2024)
This portfolio highlights climate-smart agriculture (CSA) innovations and conservation agriculture (CA) practices implemented in Kenya’s arid and semi-arid lands (ASALs) under the AICCRA project. It details innovative solutions such as drought-tolerant crop varieties, mechanized land preparation, and integrated soil and water management. Additionally, it showcases capacity-building initiatives, community engagement, and gender-inclusive strategies aimed at enhancing food security, resilience to climate change, and sustainable agriculture among the smallholder farmers